LEARNING ENGLISH WITH CHATGPT: A SECOND LANGUAGE LEARNER’S COMPANION - Amrutbhai, Parmar Himanshu; Patel, Vimal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The AI revolution, for English language learners, is a parade that is messy, swift, sometimes unsettling, and, certainly, now impossible to ignore. This article ventures deep into the landscape where ChatGPT, a language model fueled by vast data and unpredictable quirks, stands beside learners as both guide and critic, sometimes as friend and sometimes strangely mechanical taskmaster. Through abrupt sentences, a blend of scholarly and colloquial tones, and a deliberate scattering of subtle grammatical slips, we explore the unpredictable journey of using ChatGPT for English language acquisition. From its fundamental technology to practical classroom applications—and its profound limits—we unravel what it means to have a robot partner in the lifelong quest to master a second tongue. Along the way, we put charts, tables, and real anecdotes beside research studies, holding up both sides of the coin; always, perhaps, with more questions than tidy answers.